The Comparison of Spectrophotometric and TLC-Densitometric for DPPH Radical Scavenging Activity Analysis of Three Medicinal Plant Extracts - Bambang Cahyono; Christina Setyadewi M.; M. Suzery; Agustina L. N. Aminin (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2020)
In this research, Thin Layer Chromatography-Densitometry has proven to be a good method for analyzing 1, 1 diphenyl 2-picrylhydrazyl (DPPH) radical scavenging activity, since this approach displayed the similar trends with UV-Vis spectrophotometric method. Three medicinal plants collected from Semarang used to evaluate both methods. The IC50 value ranged from 25.26 - 4913.74 ppm shown by UV-Vis spectrophotometric and 24.74 – 4674.61 ppm using TLC-Densitometric. Meniran Dechlorophyllated (Phyllanthus niruri) provides the strongest antioxidant activity and the weakest de-chlorophylated parsley (Petroselinum crispum). The paired sample t-test points from a non-dechlorophylation extract using the TLC densitometry test significantly gives a lower IC50 value than the UV spectrophotometry method-has. The maximum increase of peak area under the UV light 365 nm up to 56.08 %. This evidence supports the presumption that the scavenging radical DPPH caused not only decreasing the maximum absorbance under UV light 516 nm but also increasing the absorbance under UV light ± 365 nm.